COMPARATIVE ANALYSIS OF INVESTMENT EXPENDITURES IN BUDGETS: REGIONAL ASPECT - M. N. Solomko (Вестник университета)
The high level of differentiation of the constituent entities of the Russian Federation determines different approaches to the policy of budget investment. The purpose of the paper is to identify common regional trends in the implementation of capital investments at the expense of budget funds, interregional differences and interpret it. In the study, horizontal and vertical analysis of budget investments has been made, the lack of a significant relationship between the level of budgetary security of the constituent entity of the Russian Federation and the scales of its budget investments has been shown. It has been shown that the investment activity of the constituent entities of the Russian Federation is not a determining fac tor, but an important factor of their investment attractiveness. The materials of the article can be used as an information base for further theoretical and applied research on the expenditures of regional budgets in general and the problem of budget investment in particular.